KARDIOCHIRURGIA DOROSŁYCHSurgical plasty of coronary ostia – own experience - Trzciński, Robert; Hirnle, Tomasz; Sobkowicz, Bożena; Lewczuk, Anna; Adamczuk, Anna; Dmitruk, Iwona; Juszczyk, Grzegorz; Cydzik, Mariusz; Jakubów, Piotr; Frank, Marek; Janiszewski, Wawrzyniec (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Introduce: Isolated stenosis of the coronary artery ostia is a rare disease requiring surgical intervention. Usually it is treated by coronary bypass grafting. Surgical plasty could be considered as an alternative approach saving material for bypass conduits. Aim: The aim of the study is assessment of the results of surgical plasty of coronary ostia. Material and Methods: From November 2003 to April 2007 surgical plasty of coronary ostia was performed in 5 patients. In 3 patients plasty of LCO was performed, in 2 plasty of RCO. In 2 patients concomitant bypass grafting procedure was done, in 1 valve operation. Results of surgery were assessed using intraoperative echocardiography and postoperative angiography. Results: The operation and postoperative course were successful in all patients. There were no hospital deaths, and no one required repeated surgery. Coronary angiography and echocardiography show good results of surgical plasty. Conclusions: 1. Surgical reconstruction of the coronary ostia is a safe procedure, restores physiological flow through the coronary arteries and perfusion of the myocardium. It allows one to apply in the future techniques of percutaneous coronary interventions or coronary artery bypass grafting. 2. Intraoperative transoesophageal echocardiographic examination is sufficient for assessment of results of surgical plasty.